Development, Economy, and Tourism dialogues between the South of Minas Gerais( Brasil ) and Minho ( Portugal ) (Gestão & Regionalidade, 2022)
The objective of this research was to identify approximations between the microregion of Itajubá (BR) and the District of Braga (PT) in the scope of economic, social and sustainable development, from the Economy of Culture and Creative Tourism. Data production was carried out on two fronts: census bases of the National Statistics Institute (INE) and Francisco Manuel dos Santos Foundation (PorData.pt), Portugal, and the Brazilian Institute of Geography and Statistics (IBGE) and interviews with responsible public managers for the development of culture and tourism in the municipalities involved. The field research showed the distances between the instituted and the practiced, which does not inhibit promising examples of the political protagonism of the community at the head of these processes. In both, it is important to overcome: low community participation; individualizing practices; verticalization of development initiatives; business organization of social movements for income and employment generation.
Keywords: Local development; Culture economics; Creative tourism